Bolivia and Chile on the Offensive via Mediated Public Diplomacy - Aguirre Azócar, Daniel (2016)
This article focuses on recent messaging initiatives by Bolivia and Chile within the context of public diplomacy. By means of a content analysis of messaging efforts via media platforms, it expects to ascertain the breadth and scope of competing views guided by representative literature on the subject. Moreover, by analyzing social media usage of both countries, the article will compare and contrast public diplomacy initiatives as they pertain to the Bolivian case against Chile at the International Court of Justice. In ending, the study's expected outcomes include a tentative evaluation of each side's public diplomacy actions. In addition the final analysis should provide evidence pointing toward elements that further restrict a positive shared agenda for both countries in the foreseeable future.